Morphologic and systemic alterations in obese and overweight subjects after a physical activity intervention program - Magalhães, Pedro (2007)
There are some evidences that exercise training reduces total and abdominal fat and some systemic variables with improve health benefits. The aim of this study was to analyse the variation of some morphologic and systemic variables in 16 (age=64.5±7.2) obese and overweight (BMI=31.4±5.7) type 2 diabetic patients, of both gender, during a regular physical exercise program, which consists of 35 minutes of fast walking every days of the week, during 8 months, and no diet intervention. The change was analysed with MANOVA. In total cholesterol, LDL, HDL, TG and Insulin the changes were analysed in a 4 months period and in weight, BMI, waist and blood pressure were analysed in an 8 months period. There was significant decreases on weight [F(1, 15) = 6.688; p = 0.021], BMI [F(1, 15) = 7.396; p = 0.016], waist [F(1, 15) = 43.032; p = 0.000] and LDL [F(1, 7) = 14,264; p = 0.007]. It could be concluded that the participation in this physical activity program enables the subjects to improve their morphologic and systemic parameters without alterations in their diet.